A simultaneously GSH-depleted bimetallic Cu(ii) complex for enhanced chemodynamic cancer therapy. Issue 34 (23rd July 2020) - Cao, Shuhua; Li, Xuezhao; Gao, Yong; Li, Fahui; Li, Kaoxue; Cao, Xuanxuan; Dai, Yiwen; Mao, Lirong; Wang, Shanshan; Tai, Xishi
Abstract : A bimetallic Cu(ii ) complex was developed as a novel antitumor chemodynamic therapy agent with glutathione depletion properties. Abstract : A bimetallic Cu(ii ) complex as a novel antitumor chemodynamic therapy agent with glutathione (GSH) depletion properties is successfully synthesized and well characterized. In tumor cells, the Cu 2+ ions of the complex are reduced to Cu + ions by GSH and then catalyzed by the overexpressed H2 O2 to generate highly cytotoxic hydroxyl radicals (˙OH) that kill cancer cells. The complex is quickly taken up by cancer cells and distributed in multiple organelles including mitochondria and the nucleus. The complex demonstrates good cytotoxicity toward various cancer cell lines. However, its toxicity toward normal cells is significantly lower than that toward cancer cells due to the limited expression of H2 O2 . In addition, the complex could arrest the cell cycle of the G0/G1 phase, thereby inducing apoptosis rather than necrosis.